Active-Duty Special Operations Forces Personnel Demonstrate Asymmetrical Loading Patterns during Landing Tasks. - Djafar, Tatiana E.; Johnson, Alexa K.; Poploski, Kathleen M.; Ross, Jeremy A.; Cuddy, Benjamin T.; Whiteseld, LCDR Connor R.; Sheppard, Ryan L.; Heebner, Nicholas R.; Winters, Joshua D. (Journal of Athletic Training (KnowledgeWorks Global, Ltd), 2026)
The highest incidences of musculoskeletal (MSK) injuries within the military occur at anatomical regions most impacted by jumping and landing, including the knee. Military personnel assigned to Special Operations Forces (SOF) are at particularly high risk of MSK injury due to occupational demands. To characterize changes in limb loading symmetry during walking gait from 6 to 12 months after ACLR in patients with extensor mechanism autografts using force-sensing insoles, and to compare the change in limb loading metrics between patients with bone-patellar tendon-bone (BPTB) and quadriceps tendon (QT) autograft. Cross-Sectional Study Laboratory Two hundred twenty-four uninjured active-duty male SOF personnel (age = 27.7 ± 5.0 years; mass = 83.1 ± 9.1 kg; height = 176.5 ± 5.7 cm) completed biomechanical analyses of two different drop landing tasks (double leg (DLDL) and single leg (SLDL)) and isokinetic strength testing of the quadriceps and hamstrings. Peak hip, knee, and ankle angles; hip, knee, and ankle angles at initial ground contact (@IC); and peak vertical ground reaction (VGRF) forces were identified during landing tasks. Maximum voluntary isokinetic knee extension strength (KES) and knee flexion strength (KFS) were also assessed. Participants demonstrated greater KES with their dominant limb by an average of 0.06 Nm/kg (p=0.001, d=0.219) and landed with greater force on the dominant limb during DLDL by an average of 20% bodyweight (p< 0.001, d=0.377). No asymmetries involving knee kinematics were identified. During DLDL, both limbs demonstrated similar significant correlations between knee (peak) and ankle (@IC and peak) kinematics and peak VGRF. During nondominant SLDL, knee@IC, peak knee flexion, and peak dorsiflexion significantly correlated to peak VGRF. Peak knee flexion during non-dominant SLDL correlated to non-dominant KES. Knee mechanics are important components for shock attenuation, but for this population, factors other than strength likely play a more significant role in controlling the mechanics about the knee during landing tasks.